RECOMMENDATIONS OF DIFFERENT COMMISSIONS ON WOMEN EDUCATION - Sarkar, Swagata (PEOPLE: International Journal of Social Sciences, 2019)
A nation cannot be educated without the education of women, as they play an important role in every sphere in upbringing a nation as a whole. It is true that women must be educated and efficient so that they can establish their own status and esteem. Education can only bring them light in achieving their life goals, to become self-confident and to hold a position. Women education directly or indirectly serves the development of a country. Thus, it was felt by some that providing women an education is urgent and a must deed. For it many commissions and policies were formed and differently they gave some major recommendations for women education.